Corporate Governance Country Assessment : Republic of Croatia - World Bank (Washington, DC, 2013)
Croatia's corporate governance system is framed by civil law with regulation for traded companies in part based on London securities rules and international standards for accounting and auditing. There are two public exchanges, which both have three tiers. The majority of companies are listed on the third tier, which has the lowest level of disclosure and listing requirements. The small number of companies on the first tiers has been reduced recently through the successful takeover of companies by strategic investors. The corporate governance structure in Croatia reflects several important aspects of the recent history of Croatian enterprise, including: a history of social ownership; the transition to capitalism; the on-going legacy of privatization; recent economic distress; and, regional conflict. Interest in corporate governance is rising with the potential for growth in the corporate sector being driven by privatization. Improvement in corporate governance is seen to have the potential for improving access to capital, and promoting efficient development of the new private sector. This Report on the Observance of Standards and Codes benchmarks the Croatian corporate governance system against the OECD Principles of Corporate Governance, recognized as one of the core standards underpinning international financial architecture. This ROSC highlights a number of areas where Croatia's corporate governance system can be strengthened: These can be grouped initially under four headings: disclosure of ownership and control; the role and effectiveness of shareholders meetings; the business practices of supervisory boards; and the audit practices of external auditors. The recommendations for reform are set out briefly in Section 4 and at greater length in the Annex.